Siderations Improve the Chemical Properties of Gray-Earth Soils in Uzbekistan (Eurasian Journal of Research, Development and Innovation, 2022)
Sidereal crops have a positive effect on the agrochemical properties of the soil. In the plots, when plowing green masses of peas, rye and typhon at the end of the growing season, the content of humus in the soil becomes higher by 0.03-0.06% and also has a positive effect on increasing the amount of nitrates and phosphorus. The increase in the yield of raw cotton on the plots during the introduction of siderites was 0,46–0,86; 0,48– 0,97; 0,42-0,71 t/ha. The profitability of production was 75.3-178.5 %.